Patient with False Negative RT-PCR for COVID-19 referred to Cancer Hospital for Lung Cancer Screening - Yadav, Ajay Kumar; Gnawali, Suman; Mandal, Sandip Kumar; Shrestha, Gyan Bahadur; Yuan, Gangbiao (Nepalese Journal of Cancer, 2021)
Background: To describe the characteristics and outcomes of patients with a clinical diagnosis of COVID-19 and false-negative SARS-CoV-2 reverse transcription-PCR (RT-PCR), and develop and internally validate a diagnostic risk score to predict risk of COVID-19 (including RT-PCR-negative COVID-19) among medical treatment. Case presentation: Herein, we report a 42-year-old male patient from myagdi district Nepal presenting with high grade fever, dry cough, headache and dizziness on the August 10, 2021 during second phase of COVID-19 pandemic. There is no history of hypertension and diabetes. He went for RT-PCR test at local COVID-19 screening center and reported as negative for RT-PCR test. After that he referred to Lumbini Zonal hospital for further evaluation. RT-PCT swab test was performed again and reported negative. On the chest X-Ray, there was opacity on both lungs and the patient was referred to cancer hospital for lung cancer screening. The patient underwent for HRCT chest and biochemical laboratory tests for further evaluation. The chest High Resolution Computed Tomography (HRCT) indicated ground grass opacity (GGO) with crazy paving a typical COVID-19 interstitial pneumonia. In the biochemical laboratory test, there were elevation in Leukocyte (Total WBC count), Neutrophil, Glucose, Bilirubin Direct, Bilirubin Total, SGOT/AST, SGPT/ALT and Lactate Dehydrogenase (LDH). There was low count found in Lymphocyte, Eosinophil and Monocyte. These laboratory parameters findings are typical sign of COVID-19 patients. Then patient was isolated and treatment of given according to COVID-19 treatment guidelines. On September 12, 2021, all diagnostic tests showed that patient recovered from COVID-19. Conclusion: It is safe to suggest that a symptomatic patient with typical chest HRCT and lab findings for COVID-19 should be quarantined or isolated even with 2 negative RT-PCR tests.